Survey of physical conditions of prospective athletes "Perisai Diri" Malang District branch - Wahyu Nadia Nur Khasanah; Eko Hariyanto (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
Physical conditions greatly affect the ability and skills of an athlete to master movement in a sport, especially Pencak Silat. The purpose of this research is to find out how the physical condition of the athletes at the level of prospective families of the Perisai Diri branch of Malang Regency is. This study used a descriptive quantitative research design and used survey research methods. The results of the survey research on the physical condition of Cakel (Prospective family level) of the Malang Regency branch of Perisai Diri showed that the average physical condition of the red belt level athletes or prospective families of the Malang Regency branch of Perisai Diri was included in the "Medium" category (30%) with an average score of The average is 250.66 and the percentage value of red belt level athletes or prospective families who have "Very Good" physical conditions are 0 athletes (0%), "Good" is 13 athletes (43%), "Medium" are 9 athletes ( 30%), "Less" by 5 athletes (17%) and "Very Less" by 3 athletes (10%). From this study, it can be concluded that the intensity and frequency of an athlete's exercise greatly affect the athlete's physical condition.